2004
DOI: 10.1638/03-074
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Carfentanil and Naltrexone in Domestic Goats (Capra Hircus)

Abstract: Using a crossover study design, the pharmacokinetics of carfentanil and naltrexone after i.v., i.m., and s.c. administration were determined in eight domestic goats (Capra hircus). Serial blood samples were taken up to 120 hr after carfentanil administration, and the plasma drug concentrations were determined using liquid chromatography and mass spectroscopy. All goats were immobilized with 40 microg/kg carfentanil i.m., although the resulting neurologic effects varied considerably. Plasma profiles showed rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
12
0
1
Order By: Relevance
“…Carfentanil, the active ingredient of Wildnil, is a fentanyl analogue that is approved for veterinary use as a tranquilizing agent for sedation, as a hypnotic, and as anesthesia of animals such as elephants, gazelles, goats, horses, pigs, polar bears, rhinoceroses, seals, and wolves [ 23 29 ]. It has been extensively studied in animals since it was first synthesized [ 23 , 28 – 30 , 32 , 37 , 38 , 109 ], but a few human studies have been also reported [ 31 , 33 , 34 ].…”
Section: Carfentanilmentioning
confidence: 99%
See 4 more Smart Citations
“…Carfentanil, the active ingredient of Wildnil, is a fentanyl analogue that is approved for veterinary use as a tranquilizing agent for sedation, as a hypnotic, and as anesthesia of animals such as elephants, gazelles, goats, horses, pigs, polar bears, rhinoceroses, seals, and wolves [ 23 29 ]. It has been extensively studied in animals since it was first synthesized [ 23 , 28 – 30 , 32 , 37 , 38 , 109 ], but a few human studies have been also reported [ 31 , 33 , 34 ].…”
Section: Carfentanilmentioning
confidence: 99%
“…Eight domestic goats were used for the clarification of the pharmacokinetic profile of carfentanil and naltrexone by Mutlow et al [ 29 ]. The animals were administrated with 40 μg/kg carfentanil intramuscularly, and after 30 min naltrexone (100 mg naltrexone/mg carfentanil) was administered for anesthesia reversal in several routes of administration (intravenous, intramuscular, and subcutaneous).…”
Section: Carfentanilmentioning
confidence: 99%
See 3 more Smart Citations